Struktur Populasi Kelelawar (Tylonycteris pachypus) yang Bersarang pada Bambu (Bambusa maculata) di Dusun Jangkok, Kecamatan Air Besar, Kabupaten Landak - Ari Hepi Yanti, Salomon Tri Rima Setyawati, (Universitas Tanjungpura, 2019)
Tylonycteris pachypus is included into Vespertilonidae family which nesting in bamboo (Bambusa maculata) in rubber plantation of Jangkok Hamlet, Air Besar Sub-District, Landak District. The aim of this study was to determine the population structure of bats and the characteristics of bamboo nests. Data collection was carried out from May to July 2017. The method used was Capture Mark Release Recapture (CMRR), the bats caught were marked with red-oil paint on the back. The results showed that one group of T. pachypus nesting in bamboo consisted of 2 adult males, 1 male young bat, and 6 adult females. The estimated total population of 14 estimated population is (SE ± 2,09). The bamboo cavity that is made as the nest by T. pachypus has a smooth inner-wall texture, moist, with a section length of 406 mm, a diameter of 41 mm, and it is at the altitude of 1870 mm above the ground. Cracks or inlets on bamboo as the entrance is small and narrow with a vertical length of 33 mm and a horizontal width of 8-10 mm.